2011
DOI: 10.1523/jneurosci.4717-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Amyloid-β (Aβ) Peptide-Binding Alcohol Dehydrogenase-Aβ Interaction Reduces Aβ Accumulation and Improves Mitochondrial Function in a Mouse Model of Alzheimer's Disease

Abstract: Amyloid-β (Aβ) peptide-binding alcohol dehydrogenase (ABAD), an enzyme present in neuronal mitochondria, exacerbates Aβ-induced cell stress. The interaction of ABAD with Aβ exacerbates Aβ-induced mitochondrial and neuronal dysfunction. Here, we show that inhibition of the ABAD-Aβ interaction, using a decoy peptide (DP) in vitro and in vivo, protects against aberrant mitochondrial and neuronal function and improves spatial learning/memory. Intraperitoneal administration of ABAD-DP [fused to the transduction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
124
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(129 citation statements)
references
References 42 publications
(85 reference statements)
3
124
0
2
Order By: Relevance
“…In fact, the inhibition of the Aβ-ABAD interaction has been shown to reduce Aβ accumulation and to improve mitochondrial function in transgenic mice and neuroblastoma cells (Lim et al, 2011;Yao et al, 2011). ABAD converts estrone to estradiol, a key antioxidant compound for neurone survival whose intracellular levels are decreased due to the interaction between Aβ and ABAD, a phenomenon that may contribute to Aβ-induced toxicity (Yang et al 2007;Lim et al, 2011).…”
Section: In Alzheimer´s Diseasementioning
confidence: 99%
“…In fact, the inhibition of the Aβ-ABAD interaction has been shown to reduce Aβ accumulation and to improve mitochondrial function in transgenic mice and neuroblastoma cells (Lim et al, 2011;Yao et al, 2011). ABAD converts estrone to estradiol, a key antioxidant compound for neurone survival whose intracellular levels are decreased due to the interaction between Aβ and ABAD, a phenomenon that may contribute to Aβ-induced toxicity (Yang et al 2007;Lim et al, 2011).…”
Section: In Alzheimer´s Diseasementioning
confidence: 99%
“…Ab can directly affect respiration, with a consequent increase in ROS production. Interactions of Ab with mitochondrial proteins such as amyloid binding alcohol dehydrogenase (ABAD) exacerbate the toxic effects on mitochondrial and neuronal functioning [31] (Fig. 2).…”
Section: Mitochondrial Dysfunction: Oxidative Stressmentioning
confidence: 99%
“…In addition, our study also demonstrated that HopA could not only bind to the C-terminal of Ab 1-42 directly and decrease the ABAD-Ab 1-42 interaction, but also restored ABAD activity without changing its expression. Interestingly, an ABAD decoy peptide (ABAD-DP) alleviates cognitive dysfunction in Tg mAPP/ABAD mice by restraining the ABADAb interaction (Yao et al, 2011), which indicates that ABAD-Ab interaction might be an effective target for the treatment of AD. Furthermore, HopA protected the synaptic function and LTP induction in APP/PS1 mice, which was accompanied by the improvement of spatial memory performance.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the interaction between Ab and ABAD decreases the activity of ABAD and causes mitochondrial dysfunction in patients with AD and transgenic mouse models of AD (Takuma et al, 2005). An ABAD decoy peptide with the capability of specifically disrupting ABAD-Ab interaction suppresses Ab-mediated mitochondrial toxicity (Yao et al, 2011), suggesting that this interaction may be a promising target for therapeutic intervention in AD.…”
Section: Introductionmentioning
confidence: 99%